CORRIGENDUM: Sherkatolabbasieh H, Hagh-Nazari L, Shafiezadeh S, Goodarzi N, Zangeneh MM, Zangeneh A. Ameliorative effects of the ethanolic extract of Allium saralicum R.M. Fritsch on CCl4-induced nephrotoxicity in mice: A stereological examination. - team, Editorial (Archives of Biological Sciences, 2017)
The corresponding author of the article Sherkatolabbasieh H, Hagh-Nazari L, Shafiezadeh S, Goodarzi N, Zangeneh MM, Zangeneh A. Ameliorative effects of the ethanolic extract of Allium saralicum R.M. Fritsch on CCl4-induced nephrotoxicity in mice: A stereological examination. Arch Biol Sci. 2017;69(3):535-43 has requested to change the affiliations of the authors. The affiliations of the authors are as follows: Hamidreza Sherkatolabbasieh Department of Pediatrics, School of Medicine, Lorestan University of Medical Sciences, Khoramabbad Iran, Islamic Republic of Lida Hagh-Nazari Department of Biochemistry, Faculty of Medicine, Kermanshah University of Medical Science, Kermanshah Iran, Islamic Republic of Shiva Shafiezadeh Department of Internal Medicine, Lorestan University of Medical Sciences, Khoramabbad Iran, Islamic Republic of Nader Goodarzi Department of Basic Science, Faculty of Veterinary Medicine, Razi University, Kermanshah Iran, Islamic Republic of Mohammad Mehdi Zangeneh Faculty of Veterinary Medicine, Razi University, Kermanshah Iran, Islamic Republic of Akram Zangeneh Faculty of Veterinary Medicine, Razi University, Kermanshah Iran, Islamic Republic of Link to the corrected article: https://doi.org/10.2298/ABS160914129S